Victimology Analysis of the Vulnerability of Street Children as Victims of Drug Abuse in Karawang Regency - Annisa Tri Atmaja; Deny Guntara; Yuniar Rahmatiar; Muhamad Abas (International Journal of Law Reconstruction, 2025)
The increasing incidence of drug abuse among street children in Karawang Regency has become a serious social and legal concern. As a vulnerable group, street children often fall victim to drug exploitation due to the absence of family supervision and their exposure to high-risk environments. This study aims to analyze the victimological factors that make street children vulnerable to drug abuse and to interpret this phenomenon through the Lifestyle Exposure theory. Using an empirical juridical method, this research combines normative analysis of legal regulations with field studies through interviews with street children, law enforcement officials, the National Narcotics Agency of Karawang Regency, and social institutions. The findings reveal that economic hardship, social pressure, and a lack of legal awareness significantly contribute to children’s exposure to drugs. In the context of Lifestyle Exposure theory, their street-based lifestyle increases the likelihood of contact with perpetrators and risky situations. Legally, these children qualify as potential victims requiring special protection. Therefore, integrated efforts between government institutions, law enforcement, and the community are urgently needed to strengthen prevention, protection, and rehabilitation mechanisms for street children affected by drug abuse.